The comparative characteristic of quality of life in patients with distant consequences of combat brain injury - Chernenko , Inna (Psychosomatic Medicine and General Practice, 2019)
This is a conference abstract from the II Scientific-practical conference "Psychosomatic medicine: science and practice". It is dedicated to the comparative characteristic of quality of life in patients with distant consequences of combat brain injury.